Laboratory Facilities as Predictors of Academic Performance among Maritime Students - Ernesto Berro; Romeo Calonia; Jao Alastra; Justine Asis; Ahleckz Cayao; Ruel Rendon; Judie Sozalo (JPAIR Institutional Research Journal)
This study investigates the influence of laboratory facilities on maritime students' learning and extent of delivery of instruction at the Merchant Marine Academy of Caraga Inc. It emphasizes the need for improvements to align with industry requirements and prepare students for future challenges. The research examines the impact of specific facilities like the seamanship lab, bridge simulator, and chart room. The researchers used a quantitative approach to gather data from maritime students and instructors through surveys. The analysis focused on the serviceability of the labs in terms of equipment availability, maintenance, and safety standards. The justification for the research is further supported by the findings, which indicate that most facilities are in good working order, with serviceability ranging from 77% to 87%. Interestingly, the study highlights that instructor expertise is just as important as the facilities themselves. It emphasizes that instructor experience and teaching methods significantly impact student learning, suggesting a need for investment in instructor development alongside improvements to the laboratories. In conclusion, the abstract justifies the research by demonstrating that laboratory facilities are important for maritime student learning and that there is a need for improvement in order to prepare students for the challenges of the maritime industry. The abstract outlines a methodology to investigate this and presents preliminary findings that justify further research.